Kontraversi Sejarah, Adat dan Moralitas di Minangkabau dalam Novel “Ketika Merah Putih Terkoyak” Karya Carl Chairun Dan Implikasinya terhadap Pembelajaran Bahasa dan Sastra - Suci Dwinitia; Afrini Rahmi (Bakaba, 2017)
This research is motivated by a cultural shift that is influenced by cultural development due to globalization.novel as one of the representations of society culture can be a benchmark in seeing the culture shift. The novel "Ketika Merah Putih Terkoyak" saw the development of culture with a different point of view by displaying a living story. Through this work, the author hopes that the young generation, especially the Minangkabau generation, know that great history has occurred in Minangkabau, and Minangkabau has been the center of the Indonesian government, and regional autonomy has actually been a part of history in Minangkabau. The author's hope in this case is not too exaggerated because according to what is expressed by Atmazaki (2005: 73) that the writing of literature is always interesting with the writing of history. Although many scholars claim that literary works cannot be the main ingredient of historical writing, but literary works cannot be ignored by historians. Literary works can be a reflection of the development of culture for the community can be learning materials for learners to understand the culture of a nation.